P015 Improving sleep health management in primary care: A potential role for community nurses?. (9th November 2022) - Basheti, M; Bawa, Z; Grunstein, R; Grivell, N; Saini, B; Gordon, C
Abstract: Background: Community nurses commonly care for a diverse patient population, often with complex chronic diseases. Sleep health is a key contributor to overall wellbeing and sleep disturbances/disorders frequently co-exist with comorbidities and can hasten disease progression. Community nurses are therefore ideally situated to care for sleep disturbed patients, but to what degree this is currently being undertaken is not known. Objectives: To explore community nurses' current sleep health practices and to look into their perspectives around potential change that can improve sleep health care provision. Methods: Qualitative semi-structured interviews were conducted with nurses working in community settings. Interviews were audio recorded, transcribed and thematically analysed. Results: Twenty-three Australian community nurses were interviewed. Participants frequently encountered patients with sleep disturbances/disorders with insomnia and sleep apnea being the most common presentations. Data analysis yielded three themes: 1) Sleep health in the community serviced, 2) Sleep health awareness and management, 3) Community nurses A to ZZZ of improving sleep health. Whilst sleep apnea appeared to be managed appropriately, insomnia was often mismanaged. Participants described their sleep health knowledge as deficient with the majority advocating for increased sleep-related education. Other important factors for improved sleep health care were standardised treatment/referral pathways, increased health professional collaboration and sufficient patient consult time. Conclusion: Community nurses commonly care for patients requiring increased sleep health care. However, they are currently underequipped to do so. Providing community nurses with appropriate resources, such as sleep-related education and standardised treatment frameworks could enable them to better manage sleep disturbance/disorder presentations.